Fostering 21st century skills using an online discussion forum in an English for specific purpose course - Jamalai@Jamali, Mazura; Krish, Pramela (Universiti Utara Malaysia Press, 2021)
Purpose – This study was initiated to explore students’ utilisation of the online discussion forum (ODF) via the university Learning Management System to assist English for Specific Purpose (ESP) students to execute and construct their final group task project, namely the Company Profile (CP). Methodology – A case study guided by Socio constructivism theory and Partnership of the 21st Century Learning Framework was employed. A total of 26 undergraduate students participated voluntarily in the ODF. The group project was carried out virtually among group members in three online sessions. Prior to the project, students were briefed by the instructor and questions were posted to students via the portal in stages to carry out the discussion online. Besides the online postings in the platform, students reflected on their online learning experiences in their reflective journals and took part in the interviews. The findings were qualitatively analysed and reported. Findings – The findings indicated that students value the learning experience and perceived the virtual setting as beneficial in assisting English language learning, as well as fostering the 21st century skills. The data from the online postings, reflective journals and interviews were grouped into several themes which provided significant aspects of their positive inclination in using ODF for their language learning facilitation and fostering of skills. The positive insight and impact on how the ODF assisted the students’ English language learning were realised in students’ Linguistic Attainment. Meanwhile, the idea of Flexibility Trait, Reference for Documentation, Confidence Increase and Attentiveness Provision were identified as influential factors on the students’ optimistic views on the usage of ODF. The students value the learning experience and also view the online environment as an inclusive venue to develop critical thinking, leadership, discipline, time management, and digital skills. Overall, this study revealed that practice in the virtual environment using ODF should be implemented in the English classroom with the belief that such mode of learning would contribute to the development language and enhancement of important skills for their future.Significance: The ODF platform demonstrated the potential for convenience, flexibility, and linguistic advancement amongst students for discussing and sharing knowledge relative to their CP construction and its execution. The non-threatening learning and the conducive atmosphere of their group discussion experience also supported active participation, in which passive participants had more opportunities to express their opinions confidently.